Effects of self-efficacy on frontal midline theta power and golf putting performance - Yu, Chien-Lin; Kao, Cheng-Wei; Wu, Jia-Hao; Hung, Eric; Chang, Wei-Chun; Yang, Ren-Ting; Wang, Kuo-Pin; Hung, Tsung-Min (Frontiers in Psychology, 2024)
Self-efficacy (SE), an individual's belief in their abilities to complete a task, is associated with top-down attentional control, affecting an individual's motor performance in sports.While the behavioral effects of SE are clear, research on the mechanisms underlying the effects of SE on sports performance is sparse. Our research goal is to gain a better understanding of the neurophysiological mechanisms underlying the effects of self-efficacy (SE) on sports performance. To achieve this goal, the research objective is to investigate the effect of low and high SE on frontal midline theta (Fmθ) activity, which is associated with top-down sustained attention, and motor performance. Thirty-four professional golfers were recruited to perform 60 putts, and their electroencephalographic activity was recorded during the task. The SE score was measured using a visual analog scale ranging from 0 to 10 before each putt. The scores of SE are categorized into higher SE or lower SE based on an individual's average score. Paired t test results revealed that trials with higher SE scores were associated with a higher putting success rate than trials with lower SE scores (53.3% vs 46.7%). Moreover, trials with higher SE scores were preceded by lower Fmθ than trials with lower SE scores (4.49 vs. 5.18). These findings suggested that higher SE was followed by less top-down attentional control, leading to better putting performance. Our findings support Bandura's SE theory, which posits that processes by which efficacy beliefs produce their effects are mediated by cognitive, motivational, emotional, and selection processes. This 4 Self-efficacy and golf putting performance study elucidated the intermediate processes of SE by investigating the effect of the anticipation of outcomes on sports performance and attentional control before putting.